The relationship between dental anxiety and oral health literacy with oral health-related quality of life - Mohammad Samami; Hassan Farrahi; Mahsa Alinia (BMC, 2024)
Abstract Background and Aim Dental anxiety is a prevalent issue in society, characterized by an uneasy sensation and anticipation of negative experiences in dental settings. In essence, dental anxiety, oral health literacy, and quality of life may have a relationship with each other, however, there is a shortage of evidence examining the interplay between these factors. Therefore, this study aimed to assess the relationship between dental anxiety and oral health literacy (OHL) with oral health-related quality of life (OHRQOL). Methods This is an analytical cross-sectional study conducted on 155 patients referred to the Department of Oromaxillofacial Diseases. Three questionnaires consisting of dental anxiety scale, oral health impact profile- 14, and oral health literacy adult questionnaire were used to measure anxiety, health literacy, and the quality of life-related to oral health. Scores were recorded and analyzed by IBM SPSS 24 software using independent samples T-test and ANOVA. Besides, the confirmatory modeling through the goodness of fit index of the model was applied. Results This study involved 155 participants, with a mean age of 38.44 ± 14 years. The majority were females, comprising 99 individuals (63.9%). In this study, 89 patients (57.4%) had dental anxiety. The mean OHL score in the examined participants was 9.88 ± 3.97. Both factors of anxiety (p < 0.001) and OHL (p = 0.012) had a significant effect on the OHRQOL. There was no significant difference in the mean OHRQOL among the three categories of OHL (p = 0.085). The confirmatory modeling showed that only the fourth (p = 0.065) and fifth (p = 0.146) questions of the OHL questionnaire had no significant effect on the total score of OHL. Besides, both factors of anxiety (p < 0.001) and OHL (p = 0.012) had a significant effect on OHRQOL. With an increase of one unit in anxiety, the OHRQOL score increases by 0.31 and for a one-unit increase in the OHL score, the OHRQOL score decreases by 0.66 units. Conclusion In conclusion, it seems that considering various dimensions of oral and dental health can help patients to have reduced psychological anxiety. Notably, further multicenter studies assessing diverse variables related to dental anxiety, OHL, and OHRQOL, and considering more comprehensive study designs with longitudinal follow-up could help provide insights into how changes in dental anxiety and OHL over time affect OHRQOL.